A single dose of cannabidiol (CBD) positively influences measures of stress in dogs during separation and car travel - Hunt, Alysia B. G.; Flint, Hannah E.; Logan, Darren W.; King, Tammie (Frontiers in Veterinary Science, 2023)
Many dogs experience stress when separated from their caregivers, as well as when travelling in vehicles. Pet owners employ various approaches to managing these issues, from training, to giving medications and supplements, often with mixed results. Cannabidiol (CBD) can alleviate stress and anxiety in humans but the effect it has on canine stress is less well documented. The present study aimed to understand the impact of being left alone and travelling in a car on measures of canine stress, and establish whether a single dose of a tetrahydrocannabinol (THC)-free CBD distillate could positive influence any measures of stress. In a blinded, parallel design study, a population of dogs were either left alone in a familiar room (n=21) or underwent a short car journey (n=19). A range of physiological and behavioral measures were collected pre, during and post-test. Significant changes in several stress-related measures (serum cortisol, mean ear temperature, heart rate, heart rate variability, whining and a stressed/anxious behavioral factor) were observed from baseline to test, with the car journey test paradigm eliciting a more pronounced stress response overall. The mitigating effect of CBD treatment varied by measure and test, with some indicating a significant reduction in canine stress compared to the placebo group. Additional research is required to fully understand the complex effect of CBD on canine wellbeing.